Ryabets K.A. Foreign political and legal experience of public administration in the field of water management (on the example of individual countries of the European Union) - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The system of bodies of public water management in France, Germany, Netherlands and United Kingdom was determined. The political and legal principles of their functioning are analyzed. Conclusions are made about positive and negative achievements of public water management in the designated states.